Tinjauan Hukum Tentang Tindakan Pidana Pencurian dalam Keadaan Memberatkan Berdasarkan Putusan Nomor 1261/Pid.B/2025/PN Lbp - San Mikael Sinambela; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu; Talita Sembiring; Jahya Adiputra Simbolon; Esra Natasya Br Sitepu; Gadis Prasiska Sembiring (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to analyze the legal review of the criminal act of aggravated theft based on decision number 1261/Pid.B/2025/PN Lbp. The method used is normative juridical law with a case approach. The results of the study indicate that the Panel of Judges at the Lubuk Pakam District Court stated that Wahyu Fahrezgi was legally and convincingly proven to have committed the crime of aggravated theft, as regulated in Article 363 paragraph (1) 3e and 5e of the Criminal Code. This crime was committed twice at night in the victim's workshop by damaging the door and taking many items which caused a loss of Rp. 25,000,000. In his considerations, the judge took into account the aggravating and mitigating elements, then sentenced him to two years in prison and decided to return the evidence to the victim. This study provides an overview of the application of criminal law related to aggravated theft and the judicial process that focuses on victim protection.